Proteome Analysis Revealed Changes in Protein Expression Patterns Caused by Mutations in Ehrlichia chaffeensis - Kondethimmanahalli, Chandramouli; Liu, Huitao; Ganta, Roman R. (Frontiers in Cellular and Infection Microbiology, 2019)
The tick-borne rickettsial pathogen, Ehrlichia chaffeensis, causes monocytic ehrlichiosis in people and other vertebrate hosts. Mutational analysis in E. chaffeensis genome aids in better understanding of its infection and persistence in host cells and in the development of attenuated vaccines. Our recent RNA deep sequencing study revealed that three genomic mutations caused global changes in the gene expression patterns, which in turn affect the ability of pathogen’s survival in a host and the host’s ability to induce protection against the pathogen. In this follow-up study, we document the impact of mutations on the pathogen’s global protein expression and the influence of protein abundance on a mutant’s attenuation and protection of vertebrate host against infection. iTRAQ labeling and mass spectrometry analysis of E. chaffeensis wildtype and mutants identified 564 proteins covering about 63% of the genome. Mutation in ECH_0379 gene encoding for an antiporter protein, causing attenuated growth in vertebrate hosts, led to overexpression of p28 outer membrane proteins, molecular chaperons and metabolic enzymes, while a mutation downstream to the ECH_0490 gene that caused minimal impact on the pathogen’s in vivo growth resulted in major changes in the expression of outer membrane proteins, transcriptional regulators and T4SS proteins. ECH_0660 gene mutation, causing the pathogen’s rapid clearance and offering protection against wild type infection challenge in a vertebrate host, had a minimal impact on proteome similar to our prior observations from transcriptome analysis. While the global proteome data reveled fewer translated proteins compared to the transcripts identified from RNA deep sequencing analysis, there is a great deal of correlation noted between the global proteome and transcriptome analysis. Further, global proteome analysis, including the assessment of 2D resolved total and immune proteomes revealed greater variations in the highly immunogenic p28-Omp proteins.